Relationship between organizational antecedents, job satisfaction, work performance and knowledge sharing practices among academician at Malaysia research universities - Abdullah, Nurfarahin Jasmine See; Ismail, Ismi Ariff (2011)
This work-in-progress paper present the study of relationship between organizational antecedents (OA), job satisfaction (JS), work performance(WP) and knowledge sharing practices(KSP) among academician at Malaysia Research Universities. The research objectives are to explore on the OA, JS, WP and KSP in the context of MRU. In this regard, investigation is carried out on the level of JS, WP and KSP of the respondents and whether there are significant differences in demographics and OA as well as mediation relationship between JS, WP and KSP. Mediation hypotheses posit how or what means an independent variable (OQ) affects a dependent variable (KSP) through one or more potential intervening variables or mediators (JS and WP). The relationship between JS, WP and KSP are also investigated. Each MRU’s were calculated for sample size by using online calculations. In the work-in-progress suggested further needs of the data collections and data analysis.